Home language environment of Polish children in Iceland and their secondlanguage academic achievement - Anna Katarzyna Wozniczka 1983-; Berman, Robert 1949- (2011)
The paper describes home language input of fifteen Polish immigrant children in the greater Reykjavík area and their academic achievement in Icelandic. Data were collected through semi-structured interviews, the chidren’s Icelandic language grades and from a questionnaire completed by their parents detailing the home language environment and the children’s academic achievement. Data were systematised, analysed and interpreted. Results indicated that Polish played a far more important role than Icelandic in parent-child home language interactions. However, it appeared that parents’ attitude towards Icelandic did not deter their children from achieving L2 proficiency. On the other hand, parents’ communication in Polish may have assisted their children develop language skills that transferred into Icelandic. Greinin lýsir heimamálsáreiti fimmtán pólskra innflytjendabarna á höfuðborgarsvæðinu og námsárangri þeirra í íslensku. Gagna var aflað með hálfopnum viðtölum, athugun á einkunnum barnanna í íslensku og spurningakönnun þar sem foreldrar svöruðu til um heimamálsumhverfi og námsárangur barnanna. Gögnin voru flokkuð, greind og túlkuð. Niðurstöður benda til að pólska leiki miklu stærra hlutverk en íslenska í heimamálssamskiptum foreldra og barna. Aftur á móti virtist viðhorf foreldra til íslensku ekki draga úr því að börnin tileinkuðu sér íslenskuna sem annað mál. Jafnframt virtist sem tjáning foreldra á pólsku gæti hjálpað börnunum að þróa færni í máli sem þau yfirfæra á íslensku.